Pengaruh Brand Personality dan Perceived Quality Terhadap Keputusan Pembelian dan Dampaknya pada Repurchase Intention Produk Natasha Skincare: Studi pada Pembeli Produk Natasha di Akun Shopee @Natasha Skincare Official - Mariyah Ulfa; Any Urwatul Wusko (Economic Reviews Journal, 2024)
This study aims to determine “The Influence of Brand Personality and Perceived Quality on Puchase Decision and Their Impact on repurchase intention of Natasha Skincare Producs (A Study on Buyers of Natasha Products on the Shopee Account @Natasha Skincare Official)”. This research uses a quantitative. The population in this study consists of buyers from the Shopee account @Natasha Skincare Official. The sampling technique used is purposive sampling with a total of 114 respondents. The research technique was conducted by distributing on ine questionnaires using Goegle Forms as the data collection instrument, and the results will be analyzed using SmartPLS 4.0. The research findings conclude that (1) brand personality has a positive buy not significant effect on purchase decision, (2) perceived quality has a positive and significant effect on purchase decision, (3) brand personality has a positive and significant effect on repurchase intention, (4) perceived quality has a positive and significant effect on repurchase intention, and (5) purchase decision has a positive but not significant effect on repurchase intention.